2022
DOI: 10.1007/s12072-022-10449-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic associated fatty liver disease better identifying patients at risk of liver and cardiovascular complications

Abstract: Background/purpose:A nomenclature of "metabolic associated fatty liver disease" (MAFLD) with new de nition was proposed in 2020 instead of previous "non-alcoholic fatty liver disease" (NAFLD). However, which better ts the clinical demand remains controversial. MethodsThe participants with fatty liver on ultrasonography from Taiwan bio-bank cohort were included. MAFLD was de ned as the presence of fatty liver, plus any of the following three conditions: overweight/obesity, type 2 diabetes mellitus (DM), or meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…The FIB-4 index is a marker of liver brosis based on metabolic-associated fatty liver disease. [15] The signi cance of waist circumference as a risk factor for DR in several studies may be due to fatty liver as a liver lesion in early-stage metabolic syndrome. At this stage, in ammatory cytokines and ROS-related factors might be important for the early progression of DR. A recent study demonstrated that a potent nicotinamide adenine dinucleotide phosphate oxidase 4 inhibitor was effective in treating the early pathological events of DR.…”
Section: Discussionmentioning
confidence: 99%
“…The FIB-4 index is a marker of liver brosis based on metabolic-associated fatty liver disease. [15] The signi cance of waist circumference as a risk factor for DR in several studies may be due to fatty liver as a liver lesion in early-stage metabolic syndrome. At this stage, in ammatory cytokines and ROS-related factors might be important for the early progression of DR. A recent study demonstrated that a potent nicotinamide adenine dinucleotide phosphate oxidase 4 inhibitor was effective in treating the early pathological events of DR.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the major difference between MAFLD and MASLD is the definition of metabolic dysfunction: any 1 of diabetes, obesity, and more than 2 metabolic risk factors in lean/normal weight subjects in MAFLD or at least 1 of 5 cardiometabolic criteria in MASLD. Our recent study found the diagnostic criteria of MAFLD could better identify the patients at risk of liver and cardiovascular complications than NAFLD 3 . Whether the diagnostic criteria of MASLD have an impact on the clinical outcomes compared with the missed population from the NAFLD population, that is, cryptogenic SLD, deserves further investigation.…”
mentioning
confidence: 92%
“…Our recent study found the diagnostic criteria of MAFLD could better identify the patients at risk of liver and cardiovascular complications than NAFLD. [3] Whether the diagnostic criteria of MASLD have an impact on the clinical outcomes compared with the missed population from the NAFLD population, that is, cryptogenic SLD, deserves further investigation. Third, another major difference is the definition of the inclusion of other chronic liver diseases.…”
mentioning
confidence: 99%
“…A meta-analysis has revealed significant correlation between AS and any degree of fibrosis, the severity of which amplifies this association ( 8 ). The risk of atherosclerosis increases when NAFLD progresses from simple steatosis to NASH ( 9 ).…”
Section: Introductionmentioning
confidence: 99%